2019
DOI: 10.1177/0021998319870588
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interlayer hybridization effect on burst pressure performance of composite overwrapped pressure vessels with load-sharing metallic liner

Abstract: In this study, multi-layered composite overwrapped pressure vessels for high-pressure gaseous storage were designed, modeled by finite element method and manufactured by filament winding technique. 34CrMo4 steel was selected as a load-sharing metallic liner. Glass and carbon filaments were overwrapped on the liner with a winding angle of [±11°/90°2]3 to obtain fully overwrapped composite reinforced vessel with non-identical front and back dome endings. The vessels were loaded with increasing internal pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…They also combine outstanding fatigue performance and resistance to creep and to most chemicals. However, carbon fibers alone represent the main cost driver of hydrogen storage systems and a significant overall increase in their demand is expected, so alternative reinforcing fibers have been the focus of R&D studies aiming at tank cost optimization [133][134][135].…”
Section: Fibersmentioning
confidence: 99%
“…They also combine outstanding fatigue performance and resistance to creep and to most chemicals. However, carbon fibers alone represent the main cost driver of hydrogen storage systems and a significant overall increase in their demand is expected, so alternative reinforcing fibers have been the focus of R&D studies aiming at tank cost optimization [133][134][135].…”
Section: Fibersmentioning
confidence: 99%
“…A comparison with the full model was also performed in previous studies 23 by employing a very similar COPV model for the deformational behavior of the vessel in order to validate the boundary conditions of the 1/16 3 D model. It was reported that the mechanical behavior of the COPVs in critical regions for both models showed a negligible difference.…”
Section: Finite Element Modeling Of Copvsmentioning
confidence: 99%
“…The progressive damage analysis of composite hydrogen storage vessels included the establishment of FEM and the analysis of results. ANSYS ACP was used by Kangal et al [ 21 ] to analyze the progressive damage of the glass fiber/carbon fiber hybrid composite pressure vessel. The results of hydrostatic pressure tests were compared with the results of finite-element simulation analysis and showed that numerical simulation results were in good agreement with experimental results.…”
Section: Introductionmentioning
confidence: 99%